White Cabbage Extract Reduces the Harmful_x000D_ Effects of Amiodarone on Heart Tissue in Rats - (:unkn) unknown (My University, 2020)
Objective: Amiodarone is used in the treatment of arrhythmia andhas been shown to cause side effects in various organs. White cabbage(Brassica oleracea L. var. capitata) is a widely consumed vegetable.The effects of exposure to amiodarone and white cabbageconsumption on heart tissue has not previously been investigated.We aimed to investigate the effects of white cabbage extract onamiodarone given to rats’ cardiac tissues.Material and Method: Rats were given white cabbage extract andamiodarone by gavage for seven days. Amiodarone was applied1 hour after administration of the white cabbage extract. On theeighth day, the hearts of the animals were taken and homogenized.The levels of lipid peroxidation (LPO), reduced glutathione(GSH), sialic acid (SA) and activities of glutathione-S-transferase(GST), catalase, superoxide dismutase (SOD) and tissue factor (TF)were determined.Results: The GSH level, CAT and SOD activities decreased, while theLPO and SA levels increased in the amiodarone treated group. TheWhite cabbage extract prevented any damage of the amiodaroneby decreasing the amount of LPO and SA and also strengthenedthe antioxidant defence system by increasing the amount of theGSH and SOD activities and the CAT and GST activities.Conclusion: It is suggested that the consumption of white cabbagecould be an alternative approach to the prevention of theadverse effects of amiodarone on heart tissue.

Amaç: Aritmi tedavisinde kullanılan amiodaronun çeşitli organlarda_x000D_ yan etkilere neden olduğu gösterilmiştir. Beyaz lahana (Brassica_x000D_ oleracea L. var. capitata) yaygın olarak tüketilen bir sebzedir. Amiodaron_x000D_ maruziyeti ve beyaz lahana tüketiminin kalp dokusu üzerindeki_x000D_ etkileri araştırılmamıştır. Beyaz lahana ekstraktının amiodaron_x000D_ uygulanan sıçanların kalp dokuları üzerindeki etkilerini araştırmayı_x000D_ amaçladık._x000D_ Gereç ve Yöntem: Sıçanlara yedi gün boyunca gavajla beyaz lahana_x000D_ ekstresi ve amiodaron verildi. Beyaz lahana ekstresinin uygulanmasından_x000D_ 1 saat sonra amiodaron uygulandı. Sekizinci günde,_x000D_ hayvanların kalpleri alındı ve homojenize edildi. Lipit peroksidasyon_x000D_ (LPO), indirgenmiş glutatyon (GSH), siyalik asit (SA) düzeyleri_x000D_ ile glutatyon-S-transferaz (GST), katalaz, süperoksit dismutaz (SOD)_x000D_ ve doku faktörü (TF) aktiviteleri belirlendi._x000D_ Bulgular: Amiodaron verilen grupta GSH, CAT, SOD aktiviteleri_x000D_ azalırken LPO ve SA seviyeleri arttı. Beyaz lahana, LPO ve SA miktarını_x000D_ azaltarak amiodaron zararını önledi. Ayrıca GSH düzeyleri ile_x000D_ SOD, CAT ve GST aktivitelerini artırarak antioksidan savunma sistemini_x000D_ güçlendirdi._x000D_ Sonuç: Beyaz lahana tüketiminin, amiodaronun kalp dokusunda_x000D_ olumsuz etkilerini önlemek için alternatif bir yaklaşım olabileceği_x000D_ ileri sürülebilir.
Beyaz Lahana Ekstresi Amiodaronun Sıçanlarda Kalp Dokusu Üzerindeki Zararlı Etkilerini İyileştirir